2008
DOI: 10.1248/cpb.56.423
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Anti Flaviviridae Activity of N6-, 5',3'-O- and 5',2'-O-Substituted Adenine Nucleoside Analogs

Abstract: The Flaviviridae virus family presents linear, plus sense, single-stranded RNA genome of 9.6 to 12.3-kilobases in length and is responsible for about seventy diseases, of which thirteen in humans. The viruses belonging to this family, are divided in three different genera, showing a great similarity in virion morphology, genome organization and replication strategy:1) Hepacivirus [Hepatitis C Virus (HCV)], Flavivirus [e.g. Yellow Fever Virus (YFV), Dengue Fever Virus (DFV), West Nile Virus (WNV)], and Pestivir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 64 publications
0
18
0
1
Order By: Relevance
“…To determine the reason for this, we collected 1 H NMR spectra of 38 a, [38] in which the 6-NH 2 group is not protected and the 3'-and 5'-OH groups are protected with TBDPS (to increase the solubility of the compound in an organic solvent), and 6-N-benzoyl-3',5'-O-bis-TBDPS-2'-deoxyadenosine 38 b [39] in the absence and presence of TolSCl and AgOTf (in CDCl 3 at À40 8C).…”
Section: H Nmr Spectroscopymentioning
confidence: 99%
“…To determine the reason for this, we collected 1 H NMR spectra of 38 a, [38] in which the 6-NH 2 group is not protected and the 3'-and 5'-OH groups are protected with TBDPS (to increase the solubility of the compound in an organic solvent), and 6-N-benzoyl-3',5'-O-bis-TBDPS-2'-deoxyadenosine 38 b [39] in the absence and presence of TolSCl and AgOTf (in CDCl 3 at À40 8C).…”
Section: H Nmr Spectroscopymentioning
confidence: 99%
“…39 Briefly, the expression plasmid encoding the N-terminal His-tagged C-terminal 24-amino-acid-deleted BVDV-NS5B was transformed into the Escherichia coli strain Rosetta™2 (DE3) pLysS (Novagene), and the transformants were then cultured in 5 mL of LB medium with 25 lg/mL kanamycin and 30 lg/mL chloramphenicol at 30°C overnight. Cultures were diluted into 1 L of LB medium with 25 lg/mL kanamycin and 30 lg/mL chloramphenicol and incubated at 30°C until the A 600 reached 0.6-0.7.…”
Section: Expression Of Bvdv-ns5bd24 Polymerasementioning
confidence: 99%
“…To examine this inhibition in more detail, we cloned and expressed the BVDV NS5B, 28 and studied the effects of compounds 32 and 42 on the activity of this viral protein. The enzymatic inhibition assays showed that these compounds inhibit the RNA polymerase at micromolar concentrations, in a dose dependent way, ultimately indicating that the RdRp is indeed their target.…”
Section: Isolation Of Bvdv Resistant Mutantsmentioning
confidence: 99%
“…35,36 Despite the enormous size of the conformational space for a given ligand, current docking methodologies have been successfully employed by our group in reproducing crystallographic evidences as well as to predict putative binding modes. 22,28,31,32,37 However, conformational sampling also plays an important role in calculating the binding free energy accurately and efficiently. The conformational flexibility of a given inhibitor and its receptor can be taken into account, resorting to a wise strategy that employs a rapid and lower level method such as flexible inhibitor/rigid receptor docking at the beginning (Section 3), and turning to the more accurate and quantitative method as the MM/PBSA analysis 35 sampled by molecular dynamics (MD) simulations only once the best pose has been identified and all eventual available criteria have been satisfied.…”
Section: Mm/pbsa Drug/protein Affinity Calculationsmentioning
confidence: 99%